Extracting the rules of obligation and duty from the book Lubab al-Manasik by Ibn al-Sindi (d. 993) - Sahab Darb Saleh , Youssef; Hamid Hammadi , Ahmed (Islamic Sciences Journal, 2025)
This research examines the extraction of the uṣūlī (foundational) principles of farḍ (obligatory acts) and wājib (mandatory acts) from Ibn al-Sindi’s Lubāb al-Manāsik. The study is essentially a process of deriving uṣūl (principles) from furūʿ (branches). The research plan is divided into two sections: Section One: Principles of Farḍ, comprising four subsections: Definition of farḍ linguistically and technically, The principle: “What is established by definitive evidence (dalīl qaṭʿī) is farḍ”, The principle: “Whatever is indispensable for fulfilling a farḍ is itself farḍ”, and The principle: “Farḍ indicates a single performance, not repetition.” Section Two: Principles of Wājib, comprising two subsections: The principle: “What is established by probabilistic evidence (dalīl ẓannī) is wājib”, and The principle: “Whatever is indispensable for fulfilling a wājib is itself wājib